Image Processing as Value Chain to Enhance Competitiveness in Healthcare Retail Business - Bob Foster; Muhamad Deni Johansyah (International Journal of Supply Chain Management, 2019)
In Indonesia the delaying of electronic ID card recording and rareness of E-ID card raw material mostly happened for past two years. This situation shown there’s implementation failure. Government acceleration of procurement policy has been released but still doesn’t solve the main problem itself. The delivery of blank ID card doesn’t spread evenly, many Indonesian citizen have to wait for more than 1 (one) year only for their electronic ID card being recorded and printed. For citizen this become disadvantages, there’s no proper supply chain management in delivering this blank ID from central government to province, city or district. Based on the phenomenon, the researcher aims to research whether the procurement policy, implementation of electronic ID card recording and its impact on Indonesia public trust or not. The analysis of the research problem is based the theory of policy implementation of Edwards in Subarsono (2005: 90) [1], theory effectiveness approach by Mahmudi (2005: 92) [2] adapted from Steers (1985: 53) [3] and for trust based by theory Flavian dan Giunaliu (2007) [4]. Methods used in this research are explanatory while the source and method for data collect use questionnaire and simple random sampling. The data was processed with partial least square. Result of this research showed a positive and significant impact of The Procurement Policy, Effectivity Implementation of Electronic ID card Recording on Citizen Trust. Thus the hypothesis proposed in this study was tested with PLS-SEM. Result shown procurement policy impact directly on citizen trust with path value 0,2882 greater than path value indirect impact through effectiveness implementation as much as 0,1765.